Environmental Impact Assessment of Co-firing Implementation at X Steam Power Plant, West Java - Dessy Tri Nugraheni; Rachmadhi Purwana; Udi Syahnoedi Hamzah (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
Co-firing is the activity of adding biomass to the combustion process as a mixed fuel for coal in power plants. In 2021 co-firing has been carried out at 17 PLTUs in Indonesia. The co-firing program at a steam power plant is a form of reducing coal consumption which can reduce carbon emissions while increasing the use of renewable energy without increasing investment in new power plants. PLTU X in West Java, Indonesia has implemented co-firing using sawdust biomass using the direct method without adding or modifying equipment. The use of biomass is obtained from wood-cutting waste, with a ratio of sawdust biomass usage <5%. Assessment of potential environmental impacts is carried out using the Life Cycle Assessment (LCA) method with cradle-to-gate coverage through two scenarios, namely full coal burning, and co-firing. The functional unit uses 1 kWh and the potential impact assessment method used IPCC2021 GWP100 and the CML-IA baseline. The results of the study obtained an assessment of the potential for environmental impact that could reduce the Global Warming Potential (GWP) by 0.13%, acidification by 0.40%, and eutrophication by 0.14%, but there was an increase in ozone layer depletion by 0.72%.